System frequency response model and droop coefficient setting considering renewable energy participation in frequency regulation - Song, Yuyan; Zhang, Yongjie; Zhang, Shuai; Liu, Fang; Su, Yunche; Liu, Yang (Frontiers in Energy Research, 2024)
The highly uncertain and uncontrollable power output of renewable energy sources (RES), when integrated into power systems at high penetration levels, reduces system inertia and introduces uncertain changes in system structure, parameters, and frequency response characteristics. This renders traditional frequency regulation analysis methods and frequency response models inapplicable, lacking a generalized model to describe renewable energy’s participation in frequency regulation. Thus, this paper proposes a method where RES utilize suitable means to reduce load, thereby contributing to frequency regulation. Furthermore, employing Virtual Synchronous Machine (VSM) technology, these renewable energy units emulate the inertia and droop characteristics of Synchronous Generators (SG), enabling their equivalent modeling alongside traditional generators within a single-machine aggregate model. An SFR (System Frequency Response) model integrating renewable energy’s frequency regulation has been established. This model enables the analysis of the relationships between the system’s equivalent droop coefficient and the frequency nadir, nadir time, and quasi-steady-state point. Furthermore, the required equivalent droop coefficients are proposed for various sending-end system capacities and operating conditions. Finally, the model’s validity and accuracy are confirmed through a modified WSCC 4-machine 10-bus system, offering theoretical underpinnings for stable system operation and optimized operational planning.